Self-perceived cultural competence: a cross-sectional study about nurses’ awareness and behavior - Tolentino Diaz, M. Y.; Barbato, D.; Marceca, M. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Cultural competence is a valuable and intangible heritage of knowledge, relationships and identity. Cultural competence is fundamental in nursing: sharing the objectives of all patients – not only foreigners – promotes patient’s participation in healthcare and supports nurses’ professional development, enhancing the intellectual capital that guides quality care. The aim of this study is to evaluate nurses’ selfperceived cultural competence.Study Design. This is a cross-sectional study.Methods. A self-administered cultural-competence questionnaire was used. Nurses working in hospitals and territorial healthcare settings in Rome, Italy, were involved in this study, from March 2017 to February 2018. Results. This study involved 192 nurses. The mean age was 46.2 ± 7.9. Most of the nurses (77.6%) were women. The nurses’ mean work experience was 21.4 ± 8.8 years; 65.1% of them had never attended any type of course concerning multiculturalism. The mean score of the nurses’ cultural competence was 4.19 ± 0.57 (range = 2.75–5.71). In all, 41.7% of the nurses did not consider themselves neither competent nor incompetent.Conclusion. The results show that nurses have an acceptable level of cultural competence, slightly higher in the territorial context.